Legal status experience of foreign students returnees from immigration center: a case study - Olutokunbo, Adekalu Samuel; Tanimoonwo, Idowu Grace; Cephas, Oluwaseyitan Rotimi (Science Publishing Group, 2014)
This study presents a qualitative insight of legal status experience of foreign students’ returnees from immigration center. Convenience sampling was applied in the study, and in-depth semi-structured interview was adopted to collect specific data among selected eleven (11) undergraduate foreign students, studying at a private university college, who were released from leggeng immigration deportation camp, Negeri Sembilan, Malaysia. Data were analyzed, and findings as themes were developed. Results of the study were classified into two categories. The first category indicates, the legal status challenges encountered by the students in the university. The second category reveals the students experience in the deportation camp. The study recommends with remarkable conclusion among others; initiatives to improve immigration collective services, roles of educators and school administration on foreign students’ supports services, and further suggested with a clarion call for more government supports, to improve the conditions of immigration deportation camp in Malaysia.